Farklılıkların Kesiştiği Coğrafyalar İçin Bir Öneri: Radikal Demokrasi(A Proposal for the Regions with the Intersection of Diversities: Radical Democracy) - Gürbüz ÖZDEMİR (Yönetim ve Ekonomi, 2013)
The democracy theory has renewed itself up to now with the suggested models that emerged in the face of social and political needs since ancient Greece. Nowadays, especially with post modernism paradigm effects, a new democracy need has been identified as a result of different identity demands. This need is felt especially in the Balkans, the Caucasus, and Middle East regions where diversities are dominant. New democracy model that has the potential to satisfy the needs emerged as a result of all kinds of diversities in accordance with post-modern approaches is radical democracy. In this article, ethnic, religious, cultural diversities in the Balkans, the Caucasus, and Middle East regions will be explained. Then, the relation between the democracy notion and differing needs will be taken into consideration. Finally, radical democracy will be focused in the theoretical context as a democracy proposal that will provide coexistence of all kinds of diversities by explaining new democratic paradigm needs.